Deep phenotyping of pubertal development in Norwegian children: the Bergen Growth Study 2 - Petur B. Juliusson; Ingvild S. Bruserud; Ninnie Helen Bakken Oehme; Andre Madsen; Ingvild H. Forthun; Melissa Balthasar; Karen Rosendahl; Kristin Viste; Astanand Jugessur; Lawrence M. Schell; Robert Bjerknes; Mathieu Roelants (Annals of Human Biology, 2023)
Background The Bergen Growth Study 2 (BGS2) aims to characterise somatic and endocrine changes in healthy Norwegian children using a novel methodology. Subjects and methods A cross-sectional sample of 1285 children aged 6–16 years was examined in 2016 using novel objective ultrasound assessments of breast developmental stages and testicular volume in addition to the traditional Tanner pubertal stages. Blood samples allowed for measurements of pubertal hormones, endocrine disruptive chemicals, and genetic analyses. Results Ultrasound staging of breast development in girls showed a high degree of agreement within and between observers, and ultrasound measurement of testicular volume in boys also showed small intra- and interobserver differences. The median age was 10.4 years for Tanner B2 (pubertal onset) and 12.7 years for menarche. Norwegian boys reached a pubertal testicular volume at a mean age of 11.7 years. Continuous reference curves for testicular volume and sex hormones were constructed using the LMS method. Conclusions Ultrasound-based assessments of puberty provided novel references for breast developmental stages and enabled the measurement of testicular volume on a continuous scale. Endocrine z-scores allowed for an intuitive interpretation of changing hormonal levels during puberty on a quantitative scale, which, in turn, provides opportunities for further analysis of pubertal development using machine-learning approaches.